Excess costs of post-traumatic stress disorder related to child maltreatment in Germany - Thomas Grochtdreis; Hans-Helmut König; Falk Leichsenring; Manfred E. Beutel; Lila Feix; Harald Gündel; Andrea Hermann; Melissa Hitzler; Christine Knaevelsrud; Iris-Tatjana Kolassa; Johannes Kruse; Helen Niemeyer; et al. (European Psychiatry)
Abstract Background Childhood maltreatment (CM) significantly increases the risk of developing post-traumatic stress disorder (PTSD) for which the prevalence in Europe is higher than initially assumed. While the high economic burden of PTSD is well-documented, little is known about the health care cost differences between individuals with PTSD-CM and those without PTSD in Germany. This study aimed to determine the excess health care and absenteeism costs associated with PTSD-CM in Germany.